Resources of interactive educational space as a basis for the organisation of multicultural education - N. A. Astashova; S. K. Bondyreva; O. L. Zhuk (Russian State Vocational Pedagogical University, 2019)
Introduction. The urgency of the problem of training future teachers to implement the ideas of multicultural education consists in the need to create a new school and a new person, for whom the interiorisation of human and national heritage is a unifying beginning and a stimulus for the development of society, culture, education and personality. The implementation of the resources of dialogue educational space allows this problem to be solved. A dialogue in its various modifications acts as a pedagogical tool, by which various cultural spheres are integrated and creative activity of pupils as citizens of the multicultural world is stimulated.The aim of the present publication was to present the options for the organisation of theoretical and practical training of future teachers for effective and creative professional activity in the dialogue educational space, which operates at the level of interaction of different cultures.Methodology and research methods. In the course of the research, the scientific ideas of humanistic, cultural and dialogical approaches to modern education were used and revised. The humanistic approach is the key approach in the study, since it determines the basis of multicultural education, emphasises the central position of a personality in the interethnic dialogue. The culturological approach in education is focused on the socio-cultural processes, valuable attitudes, unique traditions and customs of diverse ethnic groups, and on the adaptation of students to the available multiethnic environment when preserving national identity. The dialogical approach combines humanistic and culturological approaches, it justifies and creates interaction between different cultures based on the principles of pluralism and tolerance.Results and scientific novelty. The article reveals the purpose of multicultural education - the versatile development of a personality on the basis of universal and national values, aimed at preserving the ethnic and cultural diversity of the peoples of Russia. The authors formulated theoretical foundations of multicultural education, in which the development of multicultural dialogue of tolerance and respect for a different way of life and mental (intellectual) values of other ethnic groups are dominant aspects. The prerequisites for the development of the humanistic potential of the teacher and student are shown in the context of modelling and implementation of ethno-cultural component of education, development of intercultural interaction and cultural experience. The principles of multicultural education are characterised: continuity, differentiation and diversity, creativity, cultural integrity, three-dimensional (stereoscopic) picture of the world, multilinguality and variability. The definition of the concept of dialogue educational space is given. Dialogue educational space is considered as specially designed environment of positive multicultural cooperation between students and teachers.Practical significance. The research materials can be used in the practice of higher pedagogical education to improve the quality of training and development of multicultural competency of future teachers.